PENGARUH PENYAJIAN LAPORAN KEUANGAN DAERAH, AKSESIBILITAS LAPORAN KEUANGAN DAN AKUNTABILITAS PENGELOLAAN KEUANGAN DAERAH TERHADAP PENGGUNAAN INFORMASI KEUANGAN DARAH (STUDI KASUS PADA KABUPATEN ACEH UTARA) - Satria, Dy Ilham; Bobby, Muhammad Ahwal (Department of Accounting, Faculty of Economics & Business, 2018)
This research aims to empirically examine whether the presentation of local financial reports, accessibility of financial report and accountability of local financial management of local finacial information by the stakeholders.this research was carried out in Aceh Utara local residence using method to collect data through survey questionnaire. They were given for the stakeholder as a user of local financial information which respondents were the member of local legislative and the local Apparatures Working Units (SKPK). By the purposive sampling method, fixed get sample from 5 members of local legislative and 68 members of local Apparatures Working Units. The test and analysis use double linear regression after the reliability test, validity test andcalssical assumption test were done. The result of test showed that the presentation of local financial reports, accessibility of financial reports and accountability of local financial management understanding significant affect to the use of local financial information.